The body and sociology (Body and society. Sociology of the body in research and theoretical concepts, 2023)
The chapter introduces the reader to the topic of sociology of the body in the Polish context, taking into account various theoretical and methodological perspectives. It presents the topics of the chapters contained in the subsequent parts of the book, and also presents the achievements of researchers and scholars whose work had the greatest influence on the development of sociological reflection on the human body, as well as on the creation of the subdiscipline of sociology of the body. They include Descartes, Pierre Bourdieu, Michel Foucault, Norbert Elias, Erving Goffman, Anthony Giddens, Zygmunt Bauman, as well as representatives of other sciences: Marcel Mauss, Maurice Merleau-Ponty, Helmut Plessner, Mary Douglas, Naomi Wolf, Richard Shusterman, and feminist researchers. The chapter also presents contemporary concepts within the sociology of the body and the achievements of researchers in both global and Polish sociology.